Mental health and suicide in former professional soccer players - Russell, E. R.; McCabe, T.; Mackay, D. F.; Stewart, K.; MacLean, J. A.; Pell, J. P.; Stewart, W. (Journal of Neurology, Neurosurgery & Psychiatry, 2020)
Introduction: There is growing recognition of an association between contact sports participation and increased risk of neurodegenerative disease, including Alzheimer`s disease and chronic traumatic encephalopathy. In addition to cognitive impairment, a range of mental health disorders and suicide are proposed as diagnostic features of traumatic encephalopathy syndrome, the putative clinical syndrome associated with neurodegeneration in these populations. However, to date,epidemiological data on contact sport participation and mental health outcomes are limited. Methods: For a cohort of former professional soccer players (n=7,676) with known high neurodegenerative mortalityand their matched general population controls(n=23,028), data on mental health outcomes were obtained by individual-level record linkage to national electronic records of hospitaladmissions and death certification. Results: Compared to matched population controls, former professional soccer players showed lower risk of hospital admission for anxiety and stress related disorders, depression, drug use disorders, alcohol use disorders and bipolar and affective mood disorders. Among soccer players, there was no significant difference in risk of hospitalisation for mental health disorders between outfield players and goalkeepers. There was no significant difference in rate of death by suicide between soccer players and controls. Conclusions: Among a population of former professional soccer players with known high neurodegenerative disease mortality, hospital admissions for common mental health disorders were lower than population controls, with no difference in suicide. Our data provide support for the reappraisal of currently proposed diagnostic clinical criteria for traumatic encephalopathy syndrome, in particular the inclusion of mental health outcomes.